Interkulturowe kompetencje komunikacyjne i glottodydaktyka społeczna - Siatkowski, Stanisław (Studia Rossica Posnaniensia, 2010)
In the era of the electronic information revolution the growth of the information society, functioning and competing natural and artificial languages, new tasks connected with more and more effective intercultural (and interdisciplinary) complementary study of theory and practice problems of teaching foreign languages in proper connection with the development of new information technologies (algorithms) for language data processing have appeared. The role of these tasks and problems will be, no doubt, increasing as a result of the rapid influx of language information and needs to overcome more and more effectively and quickly the language barriers. Under these conditions caused by nowadays as well as future demands and challenges, presented in our paper social methodology in language teaching may be of crucial importance as the new theory and practice of teaching foreign languages.